Genetic determinants of COVID-19 severity and mortality: ACE1 Alu 287 bp polymorphism and ACE1, ACE2, TMPRSS2 expression in hospitalized patients - João Locke Ferreira de Araújo; Átila Duque Rossi; Jessica Maciel de Almeida; Hugo José Alves; Isabela de Carvalho Leitão; Renata Eliane de Ávila; Anna Carla Pinto Castiñeiras; Jéssica da Silva Oliveira; Rafael Mello Galliez; Marlon Daniel Lima Tonini; Débora Souza Faffe; Shana Priscila Coutinho Barroso Barroso; et al. (PeerJ)
Background The angiotensin-converting enzyme 2 (ACE2) and the transmembrane serine protease 2 (TMPRSS2) are central human molecules in the SARS-CoV-2 virus-host interaction. Evidence indicates that ACE1 may influence ACE2 expression. This study aims to determine whether ACE1, ACE2, and TMPRSS2 mRNA expression levels, along with the ACE1 Alu 287 bp polymorphism (rs4646994), contribute to the severity and mortality of COVID-19. Methods Swabs were collected in two Brazilian cities in 2020: Belo Horizonte (n = 134) and Rio de Janeiro (n = 41). A swab of mild patients in Rio de Janeiro who were not hospitalized (n = 172) was also collected. All analyzed biological material was obtained from residual diagnostic samples in 2020, prior to the emergence of SARS-CoV-2 variants of concern. ACE1, ACE2, TMPRSS2, and B2M (reference gene) expression levels were evaluated in 40 cycles of quantitative PCR. ACE1 Alu 287 bp polymorphism was genotyped using the FastStart Universal SYBR Green Master kit. Results The median age differed between clinical sites (p = 0.016), but no difference in median days of hospitalization was observed (p = 0.329). Age was associated with severity (p = 0.014) and mortality (p = 0.014) in the Belo Horizonte cohort. No alteration in ACE1, ACE2 and TMPRSS2 expression was associated with severity or mortality. ACE1 polymorphism rs4646994 did not influence the likelihood of either outcome. A meta-analysis including available data from the literature showed significant effects: the D-allele conferred risk (OR = 1.39; 95% CI [1.12–1.72]).